2019
DOI: 10.17759/jmfp.2019080207
|View full text |Cite
|
Sign up to set email alerts
|

The experience of Application of Information and Communication Technologies (ICTs) as a Tool to Enhance Learning Motivation

Abstract: The analytical review of foreign studies focuses on the utilization of information and communication technologies (ICT) in education. It considers the most popular networking technology currently used in the educational process in many countries of the world. It also exemplifies the studies demonstrating that the use of ICT can enhance learning motivation and improve academic performance among students of different ages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
0
1
0
2
Order By: Relevance
“…As Prudnikova and Poskakalova (2019) suggest, the use of such materials increases educational motivation, makes it possible to study on individual educational paths according to personal inclinations and the current level of a student's development, expands the intensity of training through the increase of the channels to receive information, and also combines a variety of teaching practices and technologies (Prudnikova and Poskakalova, 2019). However, independent studies that compared online and face-to-face education showed the latter to be more effective: students who took the online course scored lower for academic performance, satisfaction of basic psychological needs, motivation, demonstration of knowledge gained, and as a result, lower final grades (Bettinger et al, 2017;Hurlbut, 2018;Wang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…As Prudnikova and Poskakalova (2019) suggest, the use of such materials increases educational motivation, makes it possible to study on individual educational paths according to personal inclinations and the current level of a student's development, expands the intensity of training through the increase of the channels to receive information, and also combines a variety of teaching practices and technologies (Prudnikova and Poskakalova, 2019). However, independent studies that compared online and face-to-face education showed the latter to be more effective: students who took the online course scored lower for academic performance, satisfaction of basic psychological needs, motivation, demonstration of knowledge gained, and as a result, lower final grades (Bettinger et al, 2017;Hurlbut, 2018;Wang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…3. Высший -это искусственная информационная реальность, созданная с целью максимального приближения к обычной реальности с помощью электронных носителей, специальных программных и технических средств, отличающаяся высокой анимацией и интерактивностью [2,3]. Под высшим уровнем ВР нами понимается тот, который имеет четыре характеристики: 1) создание средствами программирования трехмерных изображений объек-тов; 2) возможность анимации (придание действий объектам и самому пользователю); 3) интерактивность (изменение виртуальной сцены в ответ на повороты головы или движение человека); 4) создание средствами программирования эффекта присутствия (presence) (ощущение человеком иллюзии содействия в искусственно созданной информационной реальности с предметами и/или субъектами).…”
Section: Introductionunclassified
“…В нашей стране средства ВР различных уровней используются в образовании, например. при повышении онлайн обучения [1], для повышения учебной мотивации [2], в бизнесе, в тренинговой работе и др. В Европе и США использование технологий ВР активно осуществляется в психотерапевтической практике, в психологическом консультировании и психокоррекции.…”
Section: Introductionunclassified